Analisis keuntungan usaha budidaya ikan bandeng (Chanos chanos Forsskal) dengan pemberian pakan berbeda pada Pokdakan Simarang Desa Ampekale Kecamatan Bontoa, Kabupaten Maros - Lukman Daris; Andi Masriah; Andi Nur Apung Massiseng; Febri Febri (Agrikan: Jurnal Agribisnis Perikanan, 2021)
Milkfish is a commodity from aquaculture that is in great demand by the community, both for local consumption and export commodities. In the fish farming business, including milkfish, the feeding management process is one of the efforts made to support the success of the aquaculture business because feed is one of the determining factors for the success of cultivation, both in terms of feed quantity and feed quality. In Ampekale Village, Bontoa District, Maros Regency, a group of fish cultivators (Pokdakan) where some cultivators anticipate the high price of artificial feed by substituting expired noodles and bread as a substitute for artificial feed. The purpose of this study was to analyze the level of profit for milkfish cultivators who used different feeds, namely cultivators who used feeds of (1) expired noodles or bread; (2) commercial feed; and (3) mixed feed between expired noodles or bread + commercial feed. The data obtained in this study were analyzed using variance (ANOVA) analysis to see the effect of different feeding on the profits of milkfish cultivators in the Simaranang fish cultivator group (Pokdakan), then continued with the W-Tuckey test to see the difference in profits between each cultivator. Based on the results of the analysis, it was found that the highest annual cultivation profit was obtained by cultivators who used a mixture of commercial feed and expired noodle/bread feed (Rp. 16,681,750/year) followed by cultivators who used commercial feed (Rp 9,123,000/year) and the profit. The lowest was experienced by cultivators who only used expired noodles/bread (Rp. 7,875,000/year)